Genome-Wide DNA Methylation Profile in Jejunum Reveals the Potential Genes Associated With Paratuberculosis in Dairy Cattle - Zhang, Junnan; Han, Bo; Zheng, Weijie; Lin, Shan; Li, Houcheng; Gao, Yahui; Sun, Dongxiao (Frontiers in Genetics, 2021)
The paratuberculosis causes substantial economic loss to dairy industry. Exploring functional genes and corresponding regulatory pathways related to resistance or susceptibility to paratuberculosis is essential for disease-resistance breeding. Co-analysis of genome-wide DNA methylation and transcriptome profiles is a critically important strategy to understand potential regulatory mechanism underlying the development of diseases. In this study, we characterized the profiles of DNA methylation of jejunum from nine Holstein cows in clinical, subclinical and healthy groups using whole-genome bisulfite sequencing (WGBS). The average methylation level in functional regions were 29.95% in promoter, 29.65% in 5' untranslated region (UTR), 68.24% in exons, 71.55% in introns and 72.81% in 3' UTR. A total of 3,911, 4,336, 4,094 differentially methylated genes (DMGs) were detected in clinical vs. subclinical, clinical vs. healthy, and subclinical vs. healthy comparative group, respectively. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed these DMGs were significantly enriched in specific biological processes related to immune response, such as Th1 and Th2 cell differentiation, wnt, TNF, MAPK, ECM-receptor interaction, cellular senescence, calcium and chemokine signaling pathways (q value < 0.05). The integration of information about DMGs, differentially expressed genes (DEGs) and biological functions suggested nine genes, CALCRL, TNC, GATA4, CD44, TGM3, CXCL9, CXCL10, PPARG and NFATC1, as promising candidates related to resistance/susceptibility to Mycobacterium avium subspecies paratuberculosis (MAP). This study is the high-resolution DNA methylation landscapes of the jejunum methylome across three conditions (clinical, subclinical and healthy) in dairy cows. Our investigations integrated different sources information about DMGs, DEGs and pathways, which allowed us to find nine functional genes that might have potential application value in resisting paratuberculosis in dairy cattle.